Case Report: Ciclosporin A for Refractory Multisystem Inflammatory Syndrome in Children - Suzuki, Takayuki; Suenaga, Tomohiro; Sakai, Aiko; Sugiyama, Masaya; Mizokami, Masashi; Mizukami, Ayumi; Takasago, Satoshi; Hamada, Hiromichi; Kakimoto, Nobuyuki; Takeuchi, Takashi; Ueda, Mina; Komori, Yuki; et al. (Frontiers in Pediatrics, 2022)
Multiple inflammatory syndrome in children (MIS-C) is a new syndrome involving the development of severe dysfunction in multiple organs after SARS-CoV-2 infection. Because the pathophysiology of MIS-C remains unclear, a treatment strategy has not yet been established. We experienced a 12-year-old boy who developed MIS-C at 56 days after SARS-CoV-2 infection and for whom ciclosporin A (CsA) was effective as a third-line treatment. He had a high fever on day 1, and developed a rash on the trunk, swelling in the cervical region, and palmar erythema on day 2. On days 3, he developed conjunctivitis and lip redness, and fulfilled the criteria for classical Kawasaki disease (KD). Although intravenous immunoglobulin infusion (IVIG) was started on day 4, fever persisted and respiratory distress and severe abdominal pain developed. On day 5, because he fulfilled the criteria for MIS-C, methylprednisolone pulse was started for 3 days as a second-line treatment. However, he did not exhibit defervescence and the symptoms continued. Therefore, we selected CsA as a third-line treatment. CsA was so effective that he became defervescent and his symptoms disappeared. In order to clarify the relationship with treatment and the change of clinical conditions, we examined the kinetics of 71 serum cytokines to determine their relationships with his clinical course during the three successive treatments. We found that CsA suppressed macrophage-activating cytokines such as, IL-12(p40), and IL-18 with improvement of his clinical symptoms. CsA may be a useful option for additional treatment of patients with MIS-C refractory to IVIG + methylprednisolone pulse.